Determinación de PCR y FR como prueba presuntiva de Artritis Reumatoide relacionado con los factores predisponentes en mujeres de 30 - 70 años de la Parroquia de Gualel. - Carrillo Coronel, Tatiana Gabriela (2013)
Today Rheumatoid Arthritis has been established as a major public health problem in our society, in addition to increased morbidity and mortality, short and long term, leads to disability and diminished quality of life. Ecuador not in the early diagnosis this disease, so that many patients have a false diagnosis of rheumatic fever and other ills receiving unnecessary empirical treatments that delay proper management of the disease or mostly not detected in time causing its complications of the illness, which is why this study is done to strengthen a presumptive diagnosis of Rheumatoid Arthritis; Being one of the major goals the determination of the values of C-reactive protein and rheumatoid factor as presumptive evidence of rheumatoid arthritis and its relationship with predisposing factors. The type of study was descriptive and cross-sectional, using a sample of 118 women aged 30 to 70 years who met the inclusion criteria. For the analysis of test samples were used latex agglutination rapid, qualitative and semiquantitative and predisposing factors of this disease, we used surveys where we can highlight: a diet rich in red meat and fat that contribute to the emergence of this disease, family history and a life subjected to insults and physical activities that can be toiling predisposing causes that contribute to the development of rheumatoid arthritis Key Word: Rheumatoid Arthritis, PCR, FR.